1999
DOI: 10.1038/8971
|View full text |Cite
|
Sign up to set email alerts
|

Spatial control of coated-pit dynamics in living cells

Abstract: Here we visualize new aspects of the dynamics of endocytotic clathrin-coated pits and vesicles in mammalian cells by using a fusion protein consisting of green fluorescent protein and clathrin light chain a. Clathrin-coated pits invaginating from the plasma membrane show definite, but highly limited, mobility within the membrane that is relaxed upon treatment with latrunculin B, an inhibitor of actin assembly, indicating that an actin-based framework may be involved in the mobility of these pits. Transient, mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

58
391
3
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 396 publications
(453 citation statements)
references
References 46 publications
58
391
3
1
Order By: Relevance
“…Functional and morphological control experiments are necessary to remove such doubt. Again, using clathrin-coated pits as an example, we and others have shown that when FP-tagged clathrin-light chain A (CLa) was expressed in cells in the presence of endogenous CLa, more than 96% of clathrin-coated pits visualized by immunofluorescence or with fluorescently labelled transferrin co-localize with FP-marked structures 13,14 , showing that nearly all clathrincoated pits are detected by the FP signal.…”
Section: Virus and Cell Labelingmentioning
confidence: 92%
“…Functional and morphological control experiments are necessary to remove such doubt. Again, using clathrin-coated pits as an example, we and others have shown that when FP-tagged clathrin-light chain A (CLa) was expressed in cells in the presence of endogenous CLa, more than 96% of clathrin-coated pits visualized by immunofluorescence or with fluorescently labelled transferrin co-localize with FP-marked structures 13,14 , showing that nearly all clathrincoated pits are detected by the FP signal.…”
Section: Virus and Cell Labelingmentioning
confidence: 92%
“…Involvement of the actin cortex in the mobility of GFP-Iabelled clathrin-coated pits was recently shown in living mammalian (Gaidarov et al 1999) and D. discoideum cells (Damer et al 1998; Mol Bioi Cell 9: 130a).…”
Section: Molecular Aspects Of the Internalisation Processesmentioning
confidence: 92%
“…In contrast, label for Thy-1 is neither concentrated in nor excluded from the patches or their neighboring coated pits, suggesting a relative absence of topographical constraints for this GPI-linked protein even after external cross-linking. It is known that clathrin-coated pits bud from topographically restricted membrane regions, including the uropods of polarized macrophages and neutrophils and the cleavage furrows of dividing cells (Pfeiffer et al, 1980;Oliver and Berlin, 1983) and that multiple vesicles may form from a single pit (Gaidarov et al, 1999;illustrated in Wilson et al, 2000). This, and other recent work (Blanpied et al, 2002), suggests cells can organize "hot spots" that are sites of repeated rounds of clathrin vesicle formation.…”
Section: Discussionmentioning
confidence: 99%